BUILDING RELIGIOUS MODERATION FROM AN EARLY AGE: A CASE STUDY OF LEARNING STRATEGIES IN PASRAMAN SWASTA PRANAWA - Ida Bagus Alit Arta Wiguna; Ida Ayu Made Yuni Andari (Padma Sari: Jurnal Ilmu Pendidikan, 2025)
The discourse of religious moderation in non-formal religious education is becoming increasingly relevant amid the challenges of diversity and increasing symptoms of social intolerance. This article aims to analyse learning strategies for building the values of religious moderation at an early age in Pasraman Swasta Pranawa in Mataram City. This research uses a qualitative approach with a case study method through observation, in-depth interviews, and documentation studies. The findings indicate that the dominant strategies for effectively internalising the values of tolerance, respect for differences, and social harmony are effective and contextual approaches. The example of Acarya, along with the local Hindu values-based approach known as Tat Twam Asi, plays a significant role in shaping Sisya moderate character. This article contributes to the development of a character education model based on spiritual values and local culture in the realm of Hindu religious education. The results of this study affirm the urgency of strengthening moderate learning strategies in non-formal religious institutions as part of multicultural education in Indonesia.